A Study of Changes in McDonald‘s Consumer Behaviour during Pandemic - Reddy, L. Sudershan; P. V., Ranjith; Shan, Khor Sheue; Qi, Lee Xue; San, Koh Pay; Ying, Lim Yi; Dubey, Aprajita; J., Tharuneswar; Rani, Kajal (AIBPM Publisher, 2022)
The objectives of the study is to examine the changes in McDonald’s consumer behaviour during pandemic. In 1955, McDonald’s developed the franchise system and continued expanding to become a famous fast-food brand in the world that have more than 38 000 restaurants in more than 100 countries (Rosenberg, 2020). In 2020, the pandemic of COVID-19 has spread throughout the world. COVID-19 brought negative effects to the businesses including McDonald’s and altered the consumer behaviour. Questionnaires are distributed to the respondents to collect information about their consumption behaviour in McDonald’s. This study has included the change in frequency patronizing McDonald’s, preferred service mode to order McDonald’s and the preferred payment method during the pandemic.